Energy characteristics for nanosecond current interrupter of semiconductor-magnetic pulse generator’s terminal stage - Khrysto, O. I. (Національний технічний університет "Харківський політехнічний інститут", 2023)
A semiconductor diode based on reverse current interruption is used to increase a pulse amplitude and peak power delivered on the process load. Usually, a current interrupter is located in the last stage of semiconductor-magnetic pulse generator (SMPG) and is connected in parallel to the load. Problem. Most of publications on this topic mostly concern with analysis of physical processes in the diode structure itself within its oscillating circuit, which is separated from previous SMPG’s pulse compression stages under condition of unidirectional energy transfer from the generator to the load. In this sense, the efficiency of conversion should be determined by the joint of electromagnetic interaction between non-linear compression stages, current interrupter and process load. Goal. Develop a mathematical model of nanosecond current interrupter to determine its electrical and energy characteristics as a part of high-voltage parallel circuit with magnetic pulse compression, depending on the duration and moment of current interruption, the equivalent circuit for load resistance, and to set the most optimal modes of its operation. Methodology. In this work, it is proposed to use a comprehensive approach aimed at the study of electromagnetic processes in the SMPG’s circuits with a nanosecond current interrupter, which takes into account the topology of circuit, the design parameters of saturable reactor, the magnetization curve, the equivalent load’s resistance, as well as the time parameters of power switches. Results. Analytical expressions describing the electrical and energy characteristics of the interrupter when it operating on the active load are obtained. A numerical simulation of interrupter in the SMPG’s double-loop pumping circuit is carried out, taking into account a nonlinearity of SR’s magnetization curve. Three operation modes of interrupter is described, depending on the initial moment of reverse conduction current interruption. The analysis of interrupter operation on the load with an active-capacitive component is carried out. Practical meaning. The results of research can be applied in development of high-voltage SMPG scheme with improved energy-dynamic parameters.

У даній роботі використовується комплексний підхід, спрямований на дослідження електромагнітних процесів у схемі магнітно-напівпровідникового генератора імпульсів з наносекундним переривником струму, який враховує топологію схеми, конструктивні параметри комутуючого дроселя, криву намагнічування його осердя, еквівалентний опір навантаження, а також часові параметри періодичної комутації силових ключів. Запропоновано модель наносекундного переривника струму паралельної ланки магнітного стиснення на основі експоненційного зростання його активного опору. Отримано аналітичні вирази, що описують електричні та енергетичні характеристики переривника струму при роботі на активне навантаження. Виконане числове модулювання переривника струму у двухконтурній схемі магнітного генератора імпульсів з урахуванням нелінійності кривої намагнічування комутуючих дроселів. Розглянуто три режими його роботи в залежності від моменту початку обриву струму зворотної провідності. Проведено аналіз роботи переривника струму на навантаження з активно-ємнісною складовою. Результати досліджень можуть бути застосовано при розробці високовольтних магнітно-напівпровідникових генераторів імпульсів з поліпшеними енергодинамічними параметрами.
Keywords: semiconductor-magnetic pulse generator; nanosecond current interrupter; saturable reactor; magnetization curve; numerical simulation; магнітно-напівпровідниковий генератор імпульсів; переривник струму; комутуючий дросель; крива намагнічування; числове моделювання